THE MEANING OF THE BODY IN OF DEATH TERROR - Safaat Ariful Hudda; Abdul Najib (IAIN Tulungagung, 2022)
death. Its highly contagious nature makes this disease difficult to treat. This condition forces everyone to rely on their own body’s immune system to survive. However, the negative perspective on the body, that is as an object, often makes people fall into panic, so that it can be fatal. Thus, this article was written in context to give a reflective meaning to the body with the philosophical investigation. The body itself is a facticity for